Alasdair MacIntyre and the professional practice of nursing - Sellman, Derek (Nursing philosophy, 2000)
In his attempt to explain and draw together disparate aspects of the tradition of the virtues MacIntyre develops a complex and specific concept that he terms a practice. By a practice he means to describe certain types of activities in which excellences can be pursued and that offer those engaged in a practice access to the goods internal to that practice. Sellman and Wainwright have both suggested that there are advantages to be had in understanding nursing as a practice in this MacIntyrean sense. This paper suggests that nursing should be considered as a particular type of MacIntyrean practice, and I have used the term a professional practice to identify this species. This paper also considers some of the implications of such a perspective and suggests that one benefit of thinking of nursing as a professional practice is that it may offer a route by which the virtues necessary for nursing can be identified.